PROVINCIAL FINANCIAL PERFORMANCE UNDER FISCAL AUTONOMY : EVIDENCE FROM SULAWESI AND KALIMANTAN (2022-2024) (Proceeding of SINERGY, 2026)
This study aims to analyze differences in the financial performance of provincial governments in Sulawesi and Kalimantan for the 2022–2024 period based on published data from Bank Indonesia. The study uses a quantitative approach with a comparative descriptive method through measuring the effectiveness ratio, fiscal decentralization ratio, and regional financial independence ratio. The data used are secondary data in the form of quarterly financial reports of provincial governments for the 2022–2024 fiscal years. The study population includes ten provinces, with eight provinces being selected as samples using a purposive sampling technique. The results show no significant differences in the effectiveness ratio, fiscal decentralization ratio, or financial independence ratio between provincial governments in Sulawesi and Kalimantan. All research hypotheses are accepted, indicating that the financial performance of provincial governments in both regions is relatively homogeneous within the national fiscal policy framework.